Fabrication of high refractive index TiO2 films using electron beam evaporator for all dielectric metasurfaces. (11th January 2018) - Jalil, Sohail Abdul; Ahmed, Qazi Salman; Akram, Mahreen; Abbas, Naseem; Khalid, Ayesha; Khalil, Arslan; Khalid, Muhammad Luqman; Mehar, Muhammad Mudassar; Riaz, Kashif; Mehmood, Muhammad Qasim
Abstract: Flat optics suffer meager efficiency due to plasmonic losses at visible wavelengths. This issue has been addressed in this study by the substitution of dielectric materials. For this purpose, optical parameters (real and imaginary parts of refractive index) and surface roughness of TiO2 films were optimized, which are pre-requisite for the development of highly efficient dielectric metasurface devices. Electron beam evaporator was employed to deposit various ultrathin TiO2 films with subwavelength thickness. These deposited films were further processed via annealing at various temperatures to achieve the appropriate optical parameters. SEM analysis confirmed the absence of craters, cracks and rugged type features, whereas, AFM analysis revealed the smoothness of deposited films with least roughness. High refractive index above 2.2 with minimum absorption coefficient in the visible region was studied through ellipsometry analysis. FTIR spectroscopy showed transmission over 90% from the deposited thin film on glass substrate. The results of this study would have significant implications for material processing at nanoscale and dielectric metasurface fabrication which would in turn eliminate the requirement of costly and sophisticated setups for such fabrications.